Early Mobilization For ICU-Acquired Weakness in the Critically Ill on A Ventilator - Misbakul Munir; Erna Melastuti; Muh. Abdurrouf (GLOBAL HEALTH SCIENCE GROUP, 2025)
ICU-Acquired Weakness (ICU-AW) common in critically ill patient on ventilator. This can be caused by several factors, one of which is immobilisation. ICU-AW is at risk for increased ventilator duration and mortality. This literature review aims to evaluate the positive impact of early mobilization for ICU-AW in the critically ill on a ventilator. This study used a literature review of national and international journal in Indonesia and English published between 2020-2025. This research uses several available database sources in e-resources : Pubmed, ScinceDirect, Google Scholar and Sematic Scholar. The researchers searched the literature using the keywords ”early mobilization” and “intensive care unit-Acquired Weakness” with the PCC approach. The researchers identified 864 journals, analysed them using the PRISMA method and found 10 journals that met the inclusion criteria. Out of 83 journals, 10 journals showed results that early mobilisation was effective in reducing ICU-AW in ventilator-dependent patients. Based on journal analysis, early mobilization is effective in reducing ICU-AW in patients on ventilators